Influence of Principals’ Leadership Styles on Job Performance of Teachers in Senior Secondary Schools in Edo State, Nigeria - Robinson Osarumwense Owenvbiugie; Vincent Okotako Ibadin (Research Highlights in Science and Technology Vol. 9, 2023)
The study assessed the influence of principals’ leadership styles on job performance of teachers in senior secondary schools in senior secondary schools in Edo State, Nigeria. The objectives of the study are: the extent principals who adopt autocratic administrative style of leadership influence teachers’ job performance; the extent principals who adopt democratic administrative style of leadership influence teachers’ job performance; and the extent principals who adopt laissez-faire administrative style of leadership influence teachers’ job performance. Three research questions guided the study, and a survey research design was adopted for the study. The population consisted of 400 teachers. 240 teachers were used as sample representing 60% of the population A proportionate sampling technique was adopted Two experts validated the Instrument. Cronbach alpha statistical tool was used for the reliability of the instrument and this yielded 0 70. Descriptive statistics of Mean and Standard Deviation were employed to answer all the research questions. Two null hypotheses were tested using t test statistics at 0 05 level of significance. A questionnaire titled Principals’ Leadership Style Questionnaire (PLSQ) was administered on the respondents by the researchers and two research assistants. The results showed that the respondents agreed that autocratic and laissez-faire principals’ leadership style influenced teachers job performance to a low extent, while democratic principles leadership style influenced teachers job performance to a high extent. Based on the findings and conclusion it was recommended that efforts should be made by government to organise workshops and symposia on a regular basis to ensure that principals understand the individual behaviours of their teachers to ensure good job performance.